Synchronisation des Chaleurs Synchronisation chez les Bovins dans la Wilaya de Chlef - HAMADOUCHE, Abdelkadir (My University, 2022)
This study was carried out in the wilaya of Chlef, during the period between February 2022 and June 2022, it concerns 40 cows and heifers of the Holstein, Montbéliarde, Fleckvieh breed, raised on farms under private sector. With the aim of evaluating the zootechnical performances of dairy cows and determining the strengths and weaknesses of the management of dairy cattle with regard to reproduction management, in particular that of heat synchronization reproductive performance and productivity females. from the use of the appropriate protocol (PRID Delta, use of prostaglandin F2 Alpha, GPG protocol.)
Keywords: dairy cows; fertility; reproduction